TATA KELOLA KEUANGAN PUBLIK DAN KEBIJAKAN FISKAL DALAM PERSPEKTIF ADMINISTRASI PUBLIK: SEBUAH TINJAUAN LITERATUR : TATA KELOLA KEUANGAN PUBLIK DAN KEBIJAKAN FISKAL DALAM PERSPEKTIF ADMINISTRASI PUBLIK: SEBUAH TINJAUAN LITERATUR - Kumalasari, Klara; Yusroni, Ahmad (STIA MALANG, 2026)
Fiscal policy is a strategic instrument in governance and public service delivery; however, its effectiveness is highly determined by the quality of public financial management (PFM). This article aims to analyze the relationship between PFM and fiscal policy implementation from a public administration perspective using an Integrative Literature Review approach. The data were derived from national and international journal articles, academic books, and policy documents published in 2021–2024, accessed through Google Scholar and SINTA databases. The analysis was conducted through thematic classification, critical comparison, and conceptual synthesis. The findings reveal that fiscal policy performance is influenced by four key dimensions: fiscal discipline, allocation efficiency, transparency–accountability, and institutional capacity. Moreover, digitalization of budgeting, integration of government financial systems, and strengthening public participation emerge as significant determinants in contemporary PFM practices. The study concludes that fiscal reform must be integrated with the strengthening of PFM based on good governance principles to enhance public service quality and social welfare. Keywords: public financial management, fiscal policy, public administration, accountability, integrative literature review